2017
DOI: 10.1098/rsif.2016.1002
|View full text |Cite
|
Sign up to set email alerts
|

Theoretically possible spatial accuracy of geomagnetic maps used by migrating animals

Abstract: Many migrating animals, belonging to different taxa, annually move across the globe and cover hundreds and thousands of kilometres. Many of them are able to show site fidelity, i.e. to return to relatively small migratory targets, from distant areas located beyond the possible range of direct sensory perception. One widely debated possibility of how they do it is the use of a magnetic map, based on the dependence of parameters of the geomagnetic field (total field intensity and inclination) on geographical coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
0
18
1
Order By: Relevance
“…According to Komolkin et al . 37 a bird could use a hierarchy of orientation systems such as geomagnetic navigation at very long distances, olfactory at intermediate scales and piloting for short range movements. Surprising both Pollonara et al .…”
Section: Discussionmentioning
confidence: 99%
“…According to Komolkin et al . 37 a bird could use a hierarchy of orientation systems such as geomagnetic navigation at very long distances, olfactory at intermediate scales and piloting for short range movements. Surprising both Pollonara et al .…”
Section: Discussionmentioning
confidence: 99%
“…A very recent related theoretical study suggested that GMF‐exploiting migratory birds probably need another navigation system, e.g. , an olfactory map to compensate for the variable fidelity of returning sites of the magnetic map, which is based on GMF intensity and inclination (Komolkin et al ). Nonetheless, local olfactory cues are highly dependent on temporal and spatial weather conditions, which considerably reduce the feasibility of olfactory maps in nature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ability to use declination, a much more consistent environmental cue compared to other sensory stimuli such as light, odor, and sound, might have been highly advantageous for securing a more efficient toolset for foraging or migration. A very recent related theoretical study suggested that GMFexploiting migratory birds probably need another navigation system, e.g., an olfactory map to compensate for the variable fidelity of returning sites of the magnetic map, which is based on GMF intensity and inclination (Komolkin et al 2017). Nonetheless, local olfactory cues are highly dependent on temporal and spatial weather conditions, which considerably reduce the feasibility of olfactory maps in nature.…”
Section: Discussionmentioning
confidence: 99%
“…If we make a more realistic assumption of field intensity measurement with 0.1 % accuracy (to ca. 50 nT), the accuracy of positioning degrades to 65-80 km in some areas and 43 km in others (Komolkin et al, 2017). A putative magnetic map can hardly be useful for spatial navigation at the scale of Baker's experiments.…”
Section: Behavioral Studies In Humansmentioning
confidence: 99%
“…If we accept these results as valid and reproducible, the most parsimonious explanation for them would be the magnetic map in humans, i.e., use of gradients of the geomagnetic field parameters for positioning in respect to the goal of displacement. However, it should be kept in mind that the scale of displacements of humans, either in Manchester experiments by Robin Baker (6-52 km) or in Princeton experiments in North America that attempted to replicate Manchester experiments (5-33 km) (Gould, 1985), was at the lower border of the magnetic map resolution, theoretically possible in the best-case scenario (Komolkin et al, 2017). The analysis based on long-term (>25 years) monitoring of the natural fluctuations of the geomagnetic field showed that even if the magnetic field parameters, i.e., total intensity and inclination, are measured by humans or any other animals perfectly accurately (which is certainly impossible), the theoretically achievable spatial resolution of positioning varies from 25-35 km in some areas and down to 5 km grain in others, depending on the steepness of magnetic intensity gradient, which varies geographically.…”
Section: Behavioral Studies In Humansmentioning
confidence: 99%